Force Analysis of Bench Press on Stable and Unstable Base - Hučko Branislav (Journal of Mechanical Engineering, 2016)
The contribution reviews current technologies for the measurement of performance in athletes during stationary exercise and validates the technology utilizing accelerometry. The behaviours of force during the bench press exercise on a stable and unstable base are reviewed and the results are presented. It was found that, training on an unstable base can be exploited by athletes to maximize their performance.